KAP study of contraception in clients undergoing MTP and sterilization in Gujarat, India - Patel, Rakesh; Ghosh, Runoo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Lack of awareness, knowledge and education, religious beliefs and fear of side effects are the main causes why women do not use family planning methods. To study the knowledge, attitude and practice of contraception among clients undergoing to Medical termination of pregnancy (MTP) and sterilization. Methods: This prospective study was done among 400 indoor cases at Department of Obstetrics and Gynecology in B.J. Medical college, Ahmedabad during July 2002 to October 2003. All the clients undergoing MTP and sterilization were explained and counseled about contraception with GATHER approach of family planning. After taking detail history, a thorough clinical examination of the clients was carried out with preliminary investigations. Results: Almost 58% clients were willing to accept TL method as contraceptive option, 39.5% IUCD, 1.75% OC pill method of contraception. Regarding history of side effect of contraceptive use, 17.3% condom users, 68.5% OC pill users, 63% CuT users have felt side effect. Almost 42.5% clients were operated by MTP + Lap TL, 39.5% by MTP + CuT and 14.5% by plain Lap TL. Conclusions: Efforts should be made to promote information, education and communication regarding emergency contraception targeted to all women of reproductive age group. It is important that unwanted pregnancy be prevented through effective contraceptive practice rather than abortion.